Jacopo Gelli’s Codice Cavalleresco Italiano A ‘Vindicatory’ Interpretation (Milan Law Review, 2024)
This article examines the Codice cavalleresco italiano (Italian Chivalric Code) by Jacopo Gelli (1892), which organizes the practice of dueling into a legal framework aimed at resolving conflicts among gentlemen. The content of Gelli’s work is analyzed through the lens of the anthropological-legal theory of vindicatory justice. This article’s goal is to highlight aspects of ‘regulated’ dueling that have traditionally been overshadowed by its seemingly violent nature: in particular, the primary and most important purpose that Gelli attributes to his Code, namely, the reconciliation of conflicting parties. The first part of the article explores three key characteristics essential for understanding Gelli’s Code: the concept of “chivalric custom”, the identity of the “gentlemen”, and the relationship between the Code and the duel. The second part of the article describes the structure and functioning of chivalric disputes, interpreted as a vindicatory process. It begins by introducing the notions of “offense,” “honor,” “satisfaction,” and “restoration of honor,” and then outlines the different phases of this process. Finally, the article offers some reflections on the relationship between Gelli’s code and state law, proposing a conceptualization of chivalric disputes as a “vindicatory cryptotype” in early 20th-century Italy.
Keywords: duel; honor; vindicatory justice; legal pluralism